Noise Pollution Evaluation at UFPR’s Jardim Botânico Campus in Pandemic Times - Vasconcelos, Igor Santiago de Castro; Souza, João Ricardo Boeing de; Zannin, Paulo Henrique Trombetta (National Journal of City Management, 2023)
This study aimed to evaluate the noise pollution on the Jardim Botânico campus of the Universidade Federal do Paraná (UFPR), in the municipality of Curitiba-PR, during the Coronavirus pandemic (SARS-CoV-2). The evaluation included comparing the acoustic measurements and statistical analysis of the data measured in the field with measurements taken before the pandemic by Vieira (2018). Therefore, the study aimed to identify whether there was a significant impact on the acoustic conditions in the area studied due to the restrictive measures imposed to address the public health emergency. The methodological procedures were based on characterizing the study area, defining the sampling points, collecting data in the field, evaluating the noise pollution according to NBR 10.151/2020 standards and Curitiba Municipal Law 10.625/2002, and statistical analysis of the data. The Shapiro-Wilk test was used to verify normality. The relationship between the noise levels before and during the pandemic was evaluated using analysis of variance and Tukey’s post hoc test, with a 0.05 significance level (α). The results and discussions address the values obtained and scored in the locations where the values exceeded the tolerance limit, denoting the possible causes and solutions for noise control according to the literature. We concluded that none of the points evaluated presented sound pressure levels within the limit recommended by NBR 10151/2020, indicating a noise pollution situation at the campus. The pandemic affected the minimum and average values, which were lower when compared to those recorded before the pandemic (p<0.05). At the same time, the maximum level (Lmax) values were similar to each other (p>0.05).